2000
DOI: 10.1111/j.1478-4408.2000.tb00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological treatment of effluent containing textile dyes

Abstract: Abstract:Colour removal of textile dyes from effluent was evaluated using a laboratory upflow anaerobic sludge blanket reactor. Several commercial dyes were selected to study the effect of dye structure on colour removal. The anaerobic reactor was fed with glucose, an easily biodegradable organic matter and selected individual dyes. Results show that some of the dyes are readily reduced under anaerobic conditions even at high concentration of 700 mg/l. The average removal efficiency for acid dyes using this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 6 publications
1
32
0
Order By: Relevance
“…Improper disposal of dye-containing wastewaters that cause aesthetic problems concerns not only the scientists, but is now beginning also to draw the public authority's attention and can generate toxic effects to aquatic life. Effluents from textile dyeing are constituted by complex mixtures of dyes, auxiliary chemicals, salts, acids, bases, organochlorines and sometimes heavy metals (Goncalves et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Improper disposal of dye-containing wastewaters that cause aesthetic problems concerns not only the scientists, but is now beginning also to draw the public authority's attention and can generate toxic effects to aquatic life. Effluents from textile dyeing are constituted by complex mixtures of dyes, auxiliary chemicals, salts, acids, bases, organochlorines and sometimes heavy metals (Goncalves et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates put the dye losses at between 10-15% (Vaidya and Datye, 1982). Though not generally toxic to the environment, dyes colour water bodies and may hinder light penetration thereby affecting aquatic life and limiting the utilization (Ajayi and Osibanjo, 1980;Goncalves et al, 2000). It has been reported that a typical textile effluent contains a dye mass concentration of 10-50 mg/L (Clarke and Anliker, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] Several researchers attempted treatment of textile effluent using membrane separation processes, [11,12] electro-coagulation techniques, [13,14] and biological treatment. [15,16] However, each technique has its drawbacks. For example, removal of dyes using nanofiltration (NF) requires high operating pressure and releases concentrated sludge into the environment.…”
Section: Introductionmentioning
confidence: 99%